Training Course on Seed Collection & Conservation and Nursery Management of Indigenous Silvopastoral Species - Ouled Belgacem, Azaiez; Hassan, Sawsan; Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2023)
In Tunisia, pastoral and silvopastoral lands play a crucial role as vital resources, constituting a substantial portion and significantly contributing to livestock feed requirements. Unfortunately, the excessive exploitation of these lands, involving overgrazing and wood cutting, has resulted in their deterioration and diminished productivity. Acknowledging the imperative for rehabilitation, the General Directorate of Forests (DGF) and the Office of Livestock and Pastures (OEP) are actively involved in restoration projects. Nonetheless, persistent challenges, particularly concerning the availability and quality of indigenous plant seeds and seedlings in public nurseries, pose obstacles to successful implementation. In response, the Livestock and Climate OneCGIAR initiative, specifically through its Work Package Three (WP3), is dedicated to enhancing the capacity of partners. To this end, ICARDA has organized a training course aimed at bolstering the skills and capacities of stakeholders engaged in rangeland rehabilitation. The course, covering seed management, nursery operations, and field visits, employs a participatory approach and collaborative learning, with the ultimate objective of empowering participants to adeptly handle indigenous plant seeds and cultivate healthy seedlings. The target beneficiaries encompass staff from DGF, OEP, and other development agencies, along with researchers and community-based organizations. Facilitated by Dr. Azaiez Ouled Belgacem, Dr. Sawsan Hassan, and Dr. Mounir Louhaichi, the training successfully engaged 33 participants, fostering a cohesive and knowledgeable team by the program's conclusion.